(untitled) - GFCM (Rome, 1996)
This document contains background papers presented at two technical working groups on the Marine Environment and Fisheries Resources. These include review of fisheries and environmental issues, assessment and management of demersal, shellfish and small pelagic fish.
Keywords: fisheries